MATHEMATICAL SILVER FOR ENTREPRENEURIAL MATHEMATICS - Parhusip, Hanna Arini; Nugroho, Didit Budi; Purnomo, Hindriyanto Dwi; Kawuryan, Istiarsi Saptuti Sri (PATTIMURA UNIVERSITY, 2022)
This article shows the result of entrepreneur mathematics by creating mathematical objects from silver. The objects discussed here are accessories to introduce undergraduate students to integrating several aspects of learning mathematics. These are learning geometry modernly, mathematical art, popularizing mathematics for society, introducing entrepreneurial values using mathematics, teamwork for achieving targets, and considering local heritage in mathematics. These aspects are blended into activity by creating designs and producing products based on the obtained designs. The particular product for this activity is creating silver accessories. The used research method is initiated by creating designs with the help of software where the surface equations are known. After the designs are obtained, the designs are communicated to the silver craftsman to be a partner in design testing and manufacturing of accessories products using the given designs. The size and the similarity of perceptions to the appearance of the design are discussed because the actual design is a three-dimensional image but expressed in objects to be two- dimensional objects. After productions are obtained, the accessories are managed to be promoted to the marketplace and social media as a form of entrepreneurial activity with materials starting from mathematics.